Beneficial effects of bilateral subthalamic stimulation on alexithymia in Parkinson's disease. (21st September 2018) - Dafsari, H. S.; Ray‐Chaudhuri, K.; Mahlstedt, P.; Sachse, L.; Steffen, J. K.; Petry‐Schmelzer, J. N.; Dembek, T. A.; Reker, P.; Barbe, M. T.; Visser‐Vandewalle, V.; Fink, G. R.; Timmermann, L.
Abstract : Background and purpose: Subthalamic nucleus (STN) deep brain stimulation (DBS) improves quality of life (QoL) and motor and non‐motor symptoms in advanced Parkinson's disease (PD). However, its effect on alexithymia and its relationship to other neuropsychiatric symptoms and QoL in PD is unclear. Methods: In this prospective, observational study of 39 patients with PD undergoing STN‐DBS, we examined the Parkinson's Disease Questionnaire‐8 (PDQ‐8), 20‐item Toronto Alexithymia Scale (TAS‐20), Hospital Anxiety and Depression Scale (HADS), Self‐Report Manic Inventory (SRMI), Apathy Evaluation Scale (AES), Unified Parkinson's Disease Rating Scale (UPDRS) activities of daily living, UPDRS motor examination and UPDRS complications (UPDRS‐II/‐III/‐IV) and levodopa‐equivalent daily dose (LEDD) pre‐operatively and at 5‐month follow‐up. Outcome changes were tested with Wilcoxon signed‐rank or paired t ‐test when parametric tests were applicable and corrected for multiple comparisons. The relationship between outcome changes was explored with bivariate correlations. Additionally, partial correlations between PDQ‐8 and TAS‐20 were computed controlling for HADS, SRMI and AES change scores. Predictor analyses for PDQ‐8 improvement were calculated for all baseline parameters. Results: The baseline prevalence of alexithymia was 17.9%. We observed significant beneficial effects of STN‐DBS on PDQ‐8, TAS‐20, HADS, UPDRS‐II, ‐III and ‐IV scores and significant LEDD reduction. The correlation between TAS‐20 and PDQ‐8 improvements remained significant after controlling for all other aforementioned outcomes. Predictor analyses for PDQ‐8 improvement were significant for PDQ‐8 and TAS‐20. Conclusions: This is the first report of beneficial effects of STN‐DBS on alexithymia. Alexithymia was significantly associated with QoL outcome independent of anxiety, depression, mania and apathy. Our study highlights the importance of alexithymia for holistic assessments of DBS outcomes.